Diagnosing acute pulmonary embolism: systematic review of evidence base and cost-effectiveness of imaging tests - Henzler, Thomas; Schönberg, Stefan; Fink, Christian (Journal of thoracic imaging, 2012)
Pulmonary embolism (PE) is a common disease causing significant morbidity and mortality and results in substantial socioeconomic costs to health care systems worldwide. The correct diagnosis, however, poses many challenges. As a result, ongoing research continues to develop and refine new and existing diagnostic algorithms. In this article, we systematically compare and evaluate the available evidence and cost-effectiveness of diagnostic imaging approaches for patients with suspected PE using data in PubMed and EMBASE up to February 2012. The obtained data were systemically analyzed and presented on the basis of the obtained evidence. A cost-effectiveness analysis of imaging techniques or algorithms has been summarized, if available, in dedicated paragraphs for the major issues on diagnostic imaging of PE that are discussed in this article.